Administrators' Perceptions of Motives to Offer Online Academic Degree Programs in Universities - Özcan, Hakan; Yıldırım, Soner (International Review of Research in Open and Distributed Learning, 2018)
Although the number of online academic degree programs offered by universities in Turkey has become increasingly significant in recent years, the current lack of understanding of administrators’ motives that contribute to initiating these programs suggests there is much to be learned in this field. This study aimed to investigate administrators’ perceptions of motives for offering online academic degree programs in universities in Turkey in terms of online associate degree programs, online master's degree programs, online bachelor's degree completion programs, and online bachelor's degree programs. A qualitative research method was employed for this study. Semi-structured interviews were conducted with 16 administrators from different universities’ distance education centers in Turkey and thematic analysis was applied to the data.  The research found that administrators’ motives for offering online academic degree programs mainly involve in answering to the high demand of prospective students. Six major themes were identified with regard to influencing factors for administrators’ motives: demands for programs, mission to support education, readiness of infrastructure, teaching staff as well as applicability of content, overcoming the shortage of classroom space and teachers, obtaining revenue, and gaining prestige.